Gastropods In Seagrass Beds Of Tongkeina Beach Waters, Manado North Sulawesi - Alvira Y. Bulahari; Alex D. Kambey; Anneke V. Lohoo (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2021)
The Tongkeina coastal waters have relatively extensive tidal areas. In addition to the seagrass community, there are also distinctive coastal communities such as mangroves and coral reefs. Coastal resources in this region are often used by the local community as a food source and have been used as a place of recreation and hotels as well. This is the reason for this study to find out the existence of gastropods on the seagrass beds in the Tongkeina area. It is expected that this study will provide information on the development and existence of the gastropods in coping with the pressure due to the construction of the hotel several years before. The methods of analysis used in this study including identification of gastropods, density, dominance, and diversity. The same research has been conducted several years before, and therefore this information was used as a comparison of the development of gastropods in the area. Thirty-five species (23 genera) were identified, with the highest density recorded was Nassarius gruneri, 0.8667 Individual/m², the dominance of 0.13972, and diversity (H'= 2.6853) which is greater than the results of the previous study 5 years ago (H’=1,9382). These results indicate that these waters are in the process of improving from previous environmental conditions.Keywords : Gastropod, coastal, domination, diversity, Tongkeina. ABSTRAKPerairan pesisir Tongkeina memiliki wilayah pasang surut relatif luas. Selain komunitas Lamun,   juga  terdapat komunitas khas wilayah pesisir lainnya seperti Mangrove dan Terumbu karang. Sumber daya pesisir di wilayah ini  sering digunakan  untuk kebutuhan makanan masyarakat, di samping itu telah dimanfaatkan sebagai tempat rekreasi dan  Hotel. Hal ini menjadi alasan untuk mengetahui keberadaan Gastropoda di hamparan Lamun di daerah Tongkeina.  Diharapkan dapat memberikan informasi perkembangan keberadaan Gastropoda, setelah melewati tekanan akibat dibangunnya hotel sejak beberapa tahun sebelumnya. Metoda analisis yaitu jenis-jenis Gastropoda, kepadatan, dominasi, dan keanekaragaman. Hal yang sama juga telah dilakukan beberapa tahun sebelumnya, sehingga informasi ini dapat dijadikan pembanding perkembangan Gastropoda di daerah tersebut. Diperoleh 35 spesies (23 genera), kepadatan tertinggi adalah Nassarius gruneri, 0.8667 Ind/m², dominasi sebesar 0.13972, dan keanekaragamannya (H’= 2.6853) lebih besar dari hasil penelitian  5 tahun sebelumnya yaitu . 1,9382. Hasil ini menunjukkan bahwa perairan tersebut berada dalam proses perbaikan kondisi lingkungannya.Kata Kunci : Gastropoda, pesisir, dominasi, keanekaragaman, Tongkeina.